2001
DOI: 10.1091/mbc.12.2.503
|View full text |Cite
|
Sign up to set email alerts
|

A New Model for Nuclear Envelope Breakdown

Abstract: Nuclear envelope breakdown was investigated during meiotic maturation of starfish oocytes. Fluorescent 70-kDa dextran entry, as monitored by confocal microscopy, consists of two phases, a slow uniform increase and then a massive wave. From quantitative analysis of the first phase of dextran entry, and from imaging of green fluorescent protein chimeras, we conclude that nuclear pore disassembly begins several minutes before nuclear envelope breakdown. The best fit for the second phase of entry is with a spreadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
68
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 28 publications
7
68
0
Order By: Relevance
“…Entry of 70-kDa dextran indicated that the size cut-off for passive permeability through nuclear pores had increased (Terasaki, 1994). Quantitative studies of dextran entry and time-lapse imaging of a nuclear pore GFP chimera support the idea that nuclear pore disassembly occurs during the period before nuclear envelope breakdown (Terasaki et al, 2001;Lénárt et al, 2003).…”
Section: Accumulation In the Nucleusmentioning
confidence: 59%
See 3 more Smart Citations
“…Entry of 70-kDa dextran indicated that the size cut-off for passive permeability through nuclear pores had increased (Terasaki, 1994). Quantitative studies of dextran entry and time-lapse imaging of a nuclear pore GFP chimera support the idea that nuclear pore disassembly occurs during the period before nuclear envelope breakdown (Terasaki et al, 2001;Lénárt et al, 2003).…”
Section: Accumulation In the Nucleusmentioning
confidence: 59%
“…The constant entry rate is consistent with an active process; it can be contrasted with the passive entry of 10-kDa fluorescent dextran through nuclear pores, which follows an exponential decay because its movement is determined solely by the concentration gradient (Peters, 1984;Terasaki et al, 2001). The constant rate of entry of cyclin B-GFP lasted for several minutes.…”
Section: Accumulation In the Nucleusmentioning
confidence: 60%
See 2 more Smart Citations
“…The idea has received support from subcellular 'fractionation' studies. But direct visualization of mitotic cells expressing fluorescent envelope proteins has shown that these proteins move freely throughout a single, continuous endoplasmic reticulum (ER) membrane system, with no evidence of vesicular intermediates 5,6 . These results have led to an alternative model that involves release and diffusion of envelope proteins and lipids into the ER, probably as a result of phosphorylation events, which abolish protein interactions essential for nuclear-envelope integrity.…”
mentioning
confidence: 99%